2008
DOI: 10.3892/mmr_00000073
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of transcripts and proteins modulated by the E7 oncogene in the lung tissue of E7-Tg mice by the omics approach

Abstract: Abstract. The E6 and E7 oncoproteins of human papilloma virus (HPV) type 16 have been known to cooperatively induce the immortalization and transformation of primary keratinocytes. We established an E7 transgenic mouse model to screen HPV-related biomakers using the omics approach. The methods used to identify HPV-modulated factors were genomics analysis by microarray using the Affymetrix 430 2.0 array to screen E7-modulated genes, and proteomics analysis using nano-LC-ESI-MS/MS to screen E7-modulated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Results showed downregulation of ALDH1A1 and ALDH3A1 in H1792 cells and Aldh1a1 in MDA-F471 cells, which are known to be overexpressed in KRAS-mutant LUAD CSCs, the downregulation of CCL20 in H1792 and MDA-F471, which plays a major role in the growth and metastasis of lung cancer cells, and the downregulation of Alcam and Tnf in MDA-F471, epithelial cell marker and proinflammatory cytokine, respectively [48]. These findings are consistent with other studies that stated the effects of anti-tumor agents on the CSC population using sphere-forming assay [46][47][48][49][50]57,58]. Furthermore, they motivate further investigations to determine the ability of AlgSulf n to target and affect CSCs growth and the pathway that is affected by the AlgSulf n .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Results showed downregulation of ALDH1A1 and ALDH3A1 in H1792 cells and Aldh1a1 in MDA-F471 cells, which are known to be overexpressed in KRAS-mutant LUAD CSCs, the downregulation of CCL20 in H1792 and MDA-F471, which plays a major role in the growth and metastasis of lung cancer cells, and the downregulation of Alcam and Tnf in MDA-F471, epithelial cell marker and proinflammatory cytokine, respectively [48]. These findings are consistent with other studies that stated the effects of anti-tumor agents on the CSC population using sphere-forming assay [46][47][48][49][50]57,58]. Furthermore, they motivate further investigations to determine the ability of AlgSulf n to target and affect CSCs growth and the pathway that is affected by the AlgSulf n .…”
Section: Discussionsupporting
confidence: 85%
“…QRT-PCR was performed as per the conditions detailed in Tables S1-S3. In addition, the qRT-PCR preliminary results of the cultivated spheres (n = 1) showed that the increase in the sulfation of biomimetic GAGs led to the decrease in the stemness properties of CSCs by down-regulation of some CSCs' markers ( Figure S5) [49][50][51][52][53][54][55][56]. Results showed downregulation of ALDH1A1 and ALDH3A1 in H1792 cells and Aldh1a1 in MDA-F471 cells, which are known to be overexpressed in KRAS-mutant LUAD CSCs, the downregulation of CCL20 in H1792 and MDA-F471, which plays a major role in the growth and metastasis of lung cancer cells, and the downregulation of Alcam and Tnf in MDA-F471, epithelial cell marker and proinflammatory cytokine, respectively [48].…”
Section: Discussionmentioning
confidence: 99%